Kajian tundaan dan antrian kendaraan pada fasilitas u-turn dan penerapan manajemen lalu lintas pada Jl. Let. Jend. Hertasning Kota Makassar - Djakaria, Mira Indriyani; Badaron, Siti Fauziah; Massara, Asma (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
U-turns on road sections do not completely solve the problem of traffic flow conflicts, U-turns can be one of the factors of conflict problems in the form of obstacles in the same or opposite direction. U-turn on Jalan Let. Gen. Hertasning, which is in front of the PLN office and Toko Duta Irama, has quite long queues and delays during peak hours and the distance between the two u-turns is only ±350 meters. The objectives of this research: 1) Analyze vehicle delays and queues when making a U-turn; 2) Implement traffic management for u-turns on Jalan Let Jend Hertasning. The main reference method is to use the 1997 Indonesian Capacity Manual (MKJI) method. The results obtained: 1) The queue at the u-turn obtained at the u-turn in front of the PLN office was 21.44 pcu with a queue length of 143 meters and a queue at The u-turn in front of the Ambassador Rhythm shop is 17.67 smp with a queue length of 118 meters. The delay that occurred due to the u-turn in front of the PLN office was 13.30 sec/pcu and the delay that occurred at the u-turn in front of the Cadaver shop was 11.91 sec/pcu. 2) Improve traffic management with capacity management, namely shifting the median opening in front of the PLN Office by ±150 meters, installing traffic signs in the opposite direction of the u-turn in front of Toko Duta Irama so that vehicles turning around are protected. Improvements with demand management, Jalan Toddopuli is made into a one-way road to Jalan Let Jend Hertasning on weekdays, namely Monday-Friday and a two-way road on holidays.